MODEL PENGUKURAN SERVICE QUALITYPERFORMANCE (SERVPERF) JASA TRANSPORTASI ONLINE: STUDI KASUS PADA PERILAKU KONSUMEN GO-JEK DI KOTA SEMARANG - Rustono, Rustono -; Setiawan, Andi Setiawan -; Wahyuni, Sri -; Astuti, Rif’ah Dwi (Admisi dan Bisnis, 2018)
The current study was conducted to increase of our understanding of factors performance-based modeling measure of service quality (SERVPERF) can improve the orientation of consumer behavior towards. An extensive review of the existing literature was used to identify 33 factors that affect to consumer behavior. The sampling technique used in this study is the accidental sampling method in this case, namely Go-Jek consumers in Semarang City. While for the number of research samples were 109 samples from a total of 123 samples. This research technique will use two approaches:  1). Confirmatory factor analysis, on Structural Equation Modeling (SEM); and 2). Regression Weight on Structural Equation Modeling (SEM). Results from both the qualitative and quantitative phases of the current study demonstrated that 33 factors that affect to consumer behavior can be clustered into eight basic process and 10 hypothesis were accepted. The model output in this study can provide a positive contribution to Go-Jek drivers in an effort to be able to realize Service Quality Performance (SERVPERF).  The sectors in which the Go-Jek consumers in Semarang City were not completely representative of reviews their demographics and geographical region. The findings suggest that, in order to increase of service quality (SERVPERF) of Go-Jek, Then focus on mastery of special perceived of Quality the most dominant variable that can affect the Customer Value, This is a strength study service quality (SERVPERF) of Go-Jek, then the advice and recommendation is to maintain and emphasize the element of access, which relate directly and indirectly to the mastery of service quality (SERVPERF). This study contributes to the body of knowledge on the value of the Service Quality Performance (SERVPERF).